Passive sonar with cylindrical array - Marszal, J.; Leśniak, W.; Salamon, R.; Jedel, A.; Zachariasz, K. (Archives of Acoustics, 2006)
The article presents a method of using active sonar with cylindrical array for passive monitoring of underwater sound sources. It is demonstrated that detecting a sound source and determining its bearings may be carried out with no changes in the construction of the receiver. Changing signal processing algorithms in the beamformer is all that is required. It is also demonstrated that in order to increase the accuracy of determining bearing it is possible to use high-resolution methods of spatial spectrum estimation. The methods are effective for angles of wave incidence contained in sonar’s beam width. Inaccuracies for larger angles result from uneven sampling of acoustic field distribution.